2020
DOI: 10.3389/fneur.2020.616550
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Lockdown on Movement Disorders Patients With Deep Brain Stimulation: A Multicenter Survey

Abstract: Background: The containment measures taken by Italian government authorities during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic caused the interruption of neurological activities of outpatient clinics. Vulnerable patients, as Parkinson's disease (PD) and dystonic patients with deep brain stimulation (DBS), may have an increased risk of chronic stress related to social restriction measures and may show a potential worsening of motor and psychiatric symptoms.Methods: This cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Indeed, physiotherapy and physical activity were not considered among the "essential needs" universally allowed during the 2020 lockdown in Italy. Their beneficial effect on PTs and on the falling risk is well acknowledged nowadays [12,13] and the discontinuation of physiotherapy was declared as a main factor of a detrimental in PD-related quality of life in a similar cohort from Italy collected during the same timeframe [14].…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, physiotherapy and physical activity were not considered among the "essential needs" universally allowed during the 2020 lockdown in Italy. Their beneficial effect on PTs and on the falling risk is well acknowledged nowadays [12,13] and the discontinuation of physiotherapy was declared as a main factor of a detrimental in PD-related quality of life in a similar cohort from Italy collected during the same timeframe [14].…”
Section: Discussionmentioning
confidence: 94%
“…In a large, survey-based study, the majority of people with PD (64%) reported disruptions in their medical care during the pandemic [7•]. During the early phase of the pandemic, there was decreased access to care for management of deep brain stimulation [22], botulinum toxin injections [17], and initiation of levodopa-carbidopa intestinal gel and continuous subcutaneous apomorphine infusion [23]. These disruptions extended to rehabilitative therapies; in one survey-based study, 60% of individuals with PD lost their access to rehabilitative care [12].…”
Section: Impact Of the Pandemic On Individuals With Movement Disordersmentioning
confidence: 99%
“…Those who had disruptions in their PD care or access to medications were more likely to experience symptomatic decline or increased disability [ 7 •, 25 ]. Patient-reported difficulties with deep brain stimulation devices predicted worsened symptoms [ 22 ]. In another study, one-third of those who reported worsening of PD symptoms associated this with loss of rehabilitative care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dystonia management, therefore, encompasses regular follow-ups and various strategies frequently managed in a multidisciplinary setting ( 2 ). The main treatment plan not only consists of medical [oral drugs ( 2 ), such as benzodiazepine and botulinum neurotoxin injection (BoNT) ( 12 )] and surgical approaches [i.e., deep brain stimulation (DBS) ( 2 , 11 , 13 )] but also, more recently, rehabilitation ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%